Exploring the role of intertextuality in promoting young ELL children's poetry writing and learning: a discourse analytic approach. Issue 2 (4th May 2018) - Hong, Huili
Abstract: This article probes into the social and discursive construction of intertextualities in young ELL children's poetry writing process. It aims to explore the role of intertextuality in promoting young ELL children's writing and academic learning through analysing naturally occurring classroom discourses. The research participants were 19 kindergarteners from six different cultural and linguistic backgrounds and their teacher. Primary data sources included participant observation, video recording, interviews and students' artefacts over time. Microethnographic discourse analysis is conducted to examine the teacher–student moment-to-moment classroom interactive discourses in the chosen key literacy event of writing a poem about their stapler. Data analysis showed that the ELL children's poem writing event was a robust learning process promoted by the teacher–student dynamic social and discursive construction of different intertextualities across different times and contexts. Based on the complex learning and intertextualities constructed in their writing process, the researcher advocates intertextuality as a powerful heuristic to transform the children's experiences into meaningful learning and actions.